Functionalization of nickel nanowires with a fluorophore aiming at new probes for multimodal bioanalysis - Pinheiro, Paula C. (2013)
This work reports research on the development of bimodal magnetic and fluorescent 1D nanoprobes. First, ferromagnetic nickel nanowires (NiNW) have been prepared by Ni electrodeposition in an anodic aluminum oxide (AAO) template. The highly ordered self-assembled AAO nanoporous templates were fabricated using a two-step anodization method of aluminum foil. The surface of the NiNW were then modified with polyethyleneimine (PEI) which was previously labeled with an organic dye (fluorescein isothiocyanate: FITC) via covalent bonding. The ensuing functionalized NiNW exhibited the characteristic green fluorescence of FITC and could be magnetically separated from aqueous solutions by using a NdFeB magnet. Finally, the interest of these bimodal NiNW as nanoprobes for in vitro cell separation and biolabeling was preliminary assessed in a proof of principle experiment that involved the attachment of biofunctionalized NiNW to blood cells.